THE COPING BEHAVIOR OF UNWANTED PREGNANCY IN DANIELLE STEEL'S THE GIFT: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - FAUZIYAH, UMI (2007)
The object of the research is the novel entitled The Gift by Danielle Steel. The study focuses on the major character, Maribeth, in facing her unwanted pregnancy. The aims of the study are: 1) to analyze the novel based on the structural element of the novel, 2) to analyze the major character based on the individual psychological perspective. The study uses qualitative study, In this method, the researcher used two data source, namely primary and secondary data source. The primary data source and the object of the study are the novel The Gift. While the secondary data sources are library research. The collected data is the descriptive technique. The result of the analysis shows the following conclusion. Firstly the structural elements of the novel present a good unity. Danielle Steel's employs traditional plot, begins with exposition followed by complication, climax and resolution. She tries to give a moral message through this novel that "unwanted pregnancy is valuable gift from God". She takes it as the theme of the novel. She employs from participant of third person narrator, point of view. She also use style in writing, Secondly, the result of the individual psychology analysis shows that Maribeth's personality. Maribeth's changes from bad woman into strong woman, because influenced by her problem. She has survive to cope her unwanted pregnancy.